IDENTIFYING SPATIAL PATTERNS OF A TYPE 38 HOUSE WITH AN ISLAMIC ARCHITECTURE APPROACH (CASE STUDY: MASDA 1 HOUSING COMPLEX) - Samsudin Raidi; Nur Jannatu Assholikhah (Architectural Research Journal, 2024)
A home is where humans engage in family interactions; naturally, humans are social beings who require assistance from others. In Islamic teachings, we are instructed to apply Islamic values, one of which is "hablumminannas" (ties of kinship). Implementation of this relationship includes visiting friends, relatives, and family. However, homeowners may feel discomfort when guests visit their homes. The arrangement of the house significantly influences the homeowner's discomfort when guests visit. Most housing developments by developers have arrangements such as the living room merging with the family room, bedroom doors facing directly to the living room, or the front door allowing a view towards the family room when the inner door is open. This study aims to analyze type 38 houses with spatial patterns that adhere to Islamic principles, thus bringing comfort to homeowners. The research was conducted at the Masda 1 housing complex in Sragen Regency. The method used in this research is qualitative descriptive research. The results of the study show that zoning in the house indicates several shortcomings, such as the absence of boundaries between the living room and the family room, and attention needs to be paid to the direction of the closet in the bathroom